O ensino das ciências e os saberes vividos: um estudo do ensino a partir do currículo da escola ribeirinha de Várzea no município de Parintins/AM - Melo, Hugo Levy da Silva de (2016)
The Science Teaching Study in Ribeirinhas Communities Schools from Amazonas, allows the students to approach their reality and enter to the complex universe of floodplain environment from socio-educational, socio-cultural and socioenvironmental relations, in order to understand the lived world of each apprentice fellow and on learning relationship with their parents and other community members, based on the curriculum relation, the daily life and the lived knowledge, in order to show the dynamics world local, in communication with the regional, national, global and all educational process of building knowledgeable citizens and critical readers of their realities. This dissertation aims, through its general objective, to understand the posture of the social subjects, teacher and students of the Nossa Senhora de Nazaré School from Limão de Baixo, to make a reflection on the articulation between the science teaching from the curriculum and the knowledge preexisting in the life’s history of Ribeirinhos students from Parintins, evidencing the types of effects that generate their social, cultural and historical place representations where the school is inserted. To direct the look within the school universe and community of Parintins, it was necessary to base the research in the phenomenology; unmasking the hull and navigating the research routes to discover a small community and school community, because one always wants and seeks to know each place to understand the process of teaching and learning, not only in Parintins, but in every Amazonian dimension. Each place in the Amazon has multiple relationships and can only be felt, perceived when they are lived, even for small spaces of time. Navigating, they reached at floodplain school from Paraná do Limão de Baixo, and each row was given by interviews, free and participant observation, and the use of mental maps; These procedures allowed visualizing the multi-serial teaching in the school and the dynamics of the teachings knowledge lived; all the data and results obtained through them, were translated and divided into three chapters, these being: "Desatracando Casco e Remando" (Unhooking Hull and Rowing): among Curriculum, Science Teaching and Lived Knowledge, "A travessia" (The Crossing) by the place of research; And the last chapter, "Ensino das Ciências na Escola Nossa Senhora de Nazará (Science Teaching at Nossa Senhora de Nazaré School): between the Curriculum and the Living Knowledge". This research allowed us to perceive the need to open spaces for deconstruction dialogues and thus to construct collectively a multicultural and multidimensional curricular proposal to recover the lived and practiced knowledge in order to strengthen the cultural identity of each Ribeirinho student of floodplain school, from the life’s place knowledge, enabling them to better understand their place of life and building and rebuilding their knowledge within the natural laboratory that is the floodplain